DECONSTRUCTION OF THE SOCIAL REALITY IN THE INFORMATION-QUANTUM RESONANCE - V. I. Ignatyev (Дискурс, 2016)
The relationship between social transformation and growth of information flows is examined. The effect of informational resonance is revealed and analyzed. The reasons of information ontology of modern society are identified. The mechanism of mutation of social action is revealed and analyzed. The author substantiates the statement that information explosion puts social systematic destruction. The everyday life structures immerse individuals into space of constructed alternatives to social reality. The author argues that the individualized society is becoming a reality and is acquiring a character of the «quantified social reality ». The possibility to use quantum paradigm approach in the version «of states relativity» by H. Everet in social theory is considered. The «Shadow» social actions are interpreted as hidden shadow connotations.